SH3BP4 is a negative regulator of amino acid-Rag GTPase-mTORC1 signaling - Kim, Young-Mi (2012)
Amino acids stimulate cell growth and suppress autophagy through activation of mTORC1. The activation of mTORC1 by amino acids is mediated by Rag guanosine triphosphatase (GTPase) heterodimers on the lysosome. The molecular mechanism by which amino acids regulate the Rag GTPase heterodimers remains to be elucidated. Here, we identify SH3BP4 (SH3 domain-binding protein 4) as a binding protein and a negative regulator of Rag GTPase complex. SH3BP4 binds to the inactive Rag GTPase complex through its Src homology 3 (SH3) domain under conditions of amino acid starvation and inhibits the formation of active Rag GTPase complex. As a consequence, the binding abrogates the interaction of mTORC1 with Rag GTPase complex and the recruitment of mTORC1 to the lysosome, thus inhibiting amino acid-induced mTORC1 activation and cell growth and promoting autophagy. These results demonstrate that SH3BP4 is a negative regulator of the Rag GTPase complex and amino acid-dependent mTORC1 signaling.